2018
DOI: 10.1186/s41074-018-0042-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure from motion using dense CNN features with keypoint relocalization

Abstract: Structure from motion (SfM) using imagery that involves extreme appearance changes is yet a challenging task due to a loss of feature repeatability. Using feature correspondences obtained by matching densely extracted convolutional neural network (CNN) features significantly improves the SfM reconstruction capability. However, the reconstruction accuracy is limited by the spatial resolution of the extracted CNN features which is not even pixel-level accuracy in the existing approach. Providing dense feature ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Since then, new and more robust methods have evolved. DenseSFM proposes a Structure from Motion (SfM) pipeline that uses dense CNN features with keypoint relocalization (Widya et al, 2018). Sarlin et al (2019) also use learned descriptors to improve localization robustness across large variations of appearance.…”
Section: Related Workmentioning
confidence: 99%
“…Since then, new and more robust methods have evolved. DenseSFM proposes a Structure from Motion (SfM) pipeline that uses dense CNN features with keypoint relocalization (Widya et al, 2018). Sarlin et al (2019) also use learned descriptors to improve localization robustness across large variations of appearance.…”
Section: Related Workmentioning
confidence: 99%
“…As deep learning technologies are developing, some new approaches have been introduced into the fields of keypoint detection and matching by means of convolutional neural networks [32]- [34]. For example, A research by Ono et al [32] reported a deep neural network LF-Net that predicted keypoints.…”
Section: B Keypoint Matchingmentioning
confidence: 99%
“…35The intensity of this candidate superpixel would be significantly different from those around it. In (34) and (35), th (1) (or th (2) ) stands for the threshold. Int(•) is the integer-valued function.…”
Section: ) Saliency Superpixel Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, new and more robust methods have evolved. DenseSFM proposes a Structure from Motion (SfM) pipeline that uses dense CNN features with keypoint relocalization (Widya, Torii, & Okutomi, 2018). Sarlin et al (2019) also use learned descriptors to improve localization robustness across large variations of appearance.…”
Section: Related Workmentioning
confidence: 99%